Toponymy of Bandung City in Mancapat Perspective (Quarter Typology) - Leli Yulifar; Aman Aman; Yuyu Yohana Risagarniwa (Paramita: Historical Studies Journal, 2023)
Nowadays, the community and the government tend to rename a location without recognizing its historical significance when, in fact, the naming of a place reflects a national identity, and in some areas, it incorporates mitigating elements, including the city of Bandung. For this reason, this study was conducted to discover the origins of place names in the city of Bandung with historical and other meanings to ensure that they will be taken into account by all parties when naming or renaming places/areas in Bandung. That being the case, a historical method with a toponomatology approach (toponymy) and the concept of mancapat (quarter typology) were employed in this study, resulting in a toponymy for the city of Bandung based on a naming pattern that refers to the concept of traditional urban planning (mancapat/circular pattern) which is in line with its historical meanings, with a time frame between 1810-2000. This is distinct from the patterns or concepts researchers adopt, typically referring to natural or socio-cultural phenomena (linear patterns). Therefore, the findings of this study can offer new insights into tracing the origins of specific locations through historical analysis supported by the concept of traditional Javanese planology (mancapat) or quarter typology. Thus, toponymy researchers can adopt it for other traditional inland state cities in Indonesia. Saat ini terdapat kecenderungan masyarakat juga pemerintah mengganti nama sebuah tempat  tanpa mempertimbangkan segi kesejarahannya. Padahal, penamaan tempat  tersebut menunjukkan sebuah jati diri bangsa, bahkan untuk beberapa daerah mengandung unsur mitigasi, termasuk di dalamnya wilayah Kota Bandung. Oleh karena itu, kajian ini bertujuan untuk menemukan asal-usul nama tempat   di Kota Bandung yang memiliki makna sejarah dan makna lainnya, agar menjadi pertimbangan para pihak saat akan mengganti atau memberi nama tempat/kawasan di Kota Bandung. Untuk itu, metode sejarah dengan pendekatan Toponomatology (Toponimi) dan  konsep  Mancapat (Typology Kuarter ) digunakan di dalam penelitian ini, sehingga dihasilkan Toponimi Kota Bandung berdasar pola penamaan yang mengacu kepada  konsep tata kota tradisional (mancapat/pola sirkular) yang in line dengan makna kesejarahannya, dengan bingkai waktu antara 1810-2000.  Hal ini berbeda dari pola atau konsep yang selama ini digunakan para peneliti  yang pada umumnya mengacu kepada  fenomena alam atau sosio kultural (pola linear). Dengan demikian, hasil penelitian ini dapat memberikan khazanah yang baru di dalam mengungkapkan asal-usul tempat, yakni analisis historis yang dibantu konsep planologi (tata kota) tradisional di Jawa (Mancapat) atau Typology Kuarter. Maka, para  peneliti toponimi bisa mengadopsinya untuk kota-kota tradisional pedalaman (inland state) lainnya di Nusantara.